MENGUAK TABIR MEROSOTNYA WIBAWA HUKUM DI INDONESIA - JS Panjaitan, Marojahan (Jurnal Wawasan Yuridika, 2011)
The phenomenon of disbelief among the people against the law due to the declining authority of law. This phenomenon in turn will impact the loss of public trust in government. If this situation in silenced and not find a solution, of course, will impact more widely. To restore the authority of this law, is the duty of all components of a state, and most of the government. It is based on the premise that the government as an executive agency directly applies the law, besides other institutions. In this way can be done is through law enforcement, including the attorney, advocate. Last but not least, after various legal devices to be addressed, in restoring the authority of this law is an effort to increase awareness of the legal community to implement and comply with the law well.Keywords: Legal Authority â Legal Awareness â Public Trust